Morfologi Kelenjar Aksesori Kelamin Jantan pada Trenggiling (Manis javanica) (MORPHOLOGY OF THE MALE SEX ACCESSORY GLANDS OF THE PANGOLIN (MANIS JAVANICA)) - Akmal, Yusrizal; Nisa, Chairun; Novelina, Savitri (Jurnal Veteriner; Vol 20 No 1 (2019)DO - 10.19087/jveteriner.2019.20.1.38, 2019)
The study aims to reveal the morphology of the male sex accessory glands of the pangolin at macroscopic and microscopic levels. Macroscopic observation included measurement of length and thickness of each accessory gland while microscopic observation, sample of each accessory gland was processed by histology technique with paraffin method and sliced with 3-5 ?m thickness and stained with hematoxylin-eosin (HE) staining for general structural observation, coloration of alcian blue (AB) pH 2.5 and periodic acid Schiff (PAS) to observe the distribution of acid and neutral mucopolysaccharides in each glands. The results showed that the male sex accessory glands of the pangolin consist of vesicular gland and prostate, and bulbourethral gland which were not observed macroscopically. The average length and thickness of vesicular gland were 1.07 cm and 0.41 cm, while the prostate was 1.17 cm and 0.54 cm respectively. All accessory glands were lobulated and separated with a thick connective tissue into lobes and lobules. Acinar cells in the vesicular glands were a serous type, whereas acinar cells in the prostate and bulbourethral gland were the mucous types. Secretion of vesicular gland contains neutral mucopolysaccharide with low concentrations and prostate containing neutral mucopolysaccharide with moderate con Jurnal Veteriner Maret 2019 Vol. 20 No. 1 : 38 - 47 pISSN: 1411-8327; eISSN: 2477-5665 DOI: 10.19087/jveteriner.2019.20.1.38 Terakreditasi Nasional, Dirjen Penguatan Riset dan Pengembangan, online pada http://ojs.unud.ac.id/index.php/jvet Kemenristek Dikti RI S.K. No. 36a/E/KPT/2016 39 centrations, and did not secrete acid mucopolysaccharide. Secretion of bulbourethral glands contains neutral and acidic mucopolysaccharide with strong concentrations. Macroscopically the bulbourethral gland is not observed but has a high carbohydrate which acts as to produce of cement plasma and rinsing urethra from urine.